TIME BUDGET PRESSURE, KOMPETENSI DAN INDEPENDENSI TERHADAP AUDITOR PERFORMENT - Rahman, Kristanti; Anggraeni, Rahayu (JURNAL EKONOMI, 2023)
This study aims to determine the effect of Time Budget Pressure, Kompetensi Dan Independensi Terhadap Auditor Performent. The data used is primary data obtained by distributing questionnaires to KAP (Public Accounting Firm) in DKI Jakarta. The number of samples in this study amounted to 80. Data analysis in this study used Multiple Regression analysis and MRA (Moderating Regression Analysis). The results showed that 1) Time Budget Pressure affects Auditor Performance, 2) Competence affects Auditor Performance, 3) independence affects Auditor Performance.